A 27.5-My underlying periodicity detected in extinction episodes of non-marine tetrapods. (2nd November 2021) - Rampino, Michael R.; Caldeira, Ken; Zhu, Yuhong
ABSTRACT: Non-marine tetrapods (amphibians, reptiles, birds and mammals) have apparently experienced at least 10 distinct episodes of intensified extinctions over the past 300 My. Eight of these ten non-marine extinction events are concurrent with known marine-extinction episodes, which previously yielded evidence for an underlying period of 26.4 to 27.3 My. We performed circular spectral analysis and Fourier transform analysis of the ages of the ten recognised tetrapod-extinction events, and detected a statistically significant (99% confidence) underlying periodicity of 27.5 My. We also find that the eight coeval non-marine/marine-extinction pulses all occurred at the times of eruptions of Large Igneous Provinces (LIPs) (continental flood-basalts and oceanic plateaus), with potentially severe environmental effects. Three of these co-extinction episodes are further correlated with the ages of the three largest (≥100-km diameter) impact craters of the last 260 My, which are also apparently capable of causing extinction events. These findings suggest that global cataclysmal events with an underlying periodicity of 27.5 My were the cause of the coordinated periodic extinction episodes of non-marine tetrapods and marine organisms.